Hubungan Persepsi Konsumen, Kualitas Produk Dan Harga Terhadap Pembelian Ulang (Studi Kasus Pada Pabrik Tahu Cik Lan Purwodadi) - Pratiwi, Desy Niken; , Drs. Sri Padmantyo, MBA (2016)
The purpose of this study to determine consumer perceptions have links to purchase again, to find out the price of having relation to the performance of the purchase and to determine the quality of the products have a relationship to re-purchase. The population in this study is the consumer or the customer who came in to Know Cik Lan Purwodadi, in etermining the sample used purposive sampling technique of "sampling taken with a certain considerations". The criteria in this study is konsmen Know Cik Lan Purwodadi while the sample of 100 respondents. Based on the results of Chi Square is known there is a connection between consumers' perceptions of repeat purchases. There is a relationship between the quality of product to purchase again. There is a correlation between the price of the purchase. The result meant customer satisfaction first and an important issue in determining the selection of a product, in this case means the factory Know Cik Lan Purwodadi have a product that really well tested on quality, thus consumers prefer and choose products that have quality good compared with other similar products that can meet the needs and desires.